The demand and supply of political campaign financing in Tanzania and Uganda during the 2010s - Moses Khisa; Jamal B. Msami; Ole Therkildsen (Danish Institute for International Studies (DIIS), 2022)
Campaign financing is defined as money and other resources used by parties and candidates during primary, parliamentary, or presidential elections to secure nomination and election to political office. In this paper, we develop a demandsupply framework for analysing and understanding such financing in newly democratising poor countries, exemplified by Tanzania and Uganda. Like other African countries, both countries operate a first-past-the-post electoral system, and both experienced a double transition towards political and economic liberalisation beginning in the 1980s. This has increased the cost to parties and candidates of being elected to public office. We make estimates of the orders of magnitude and sources of campaign financing in the two elections in both countries during the early and mid-2010s. Some 80+ members of parliament in each country were interviewed in 2017 to provide such information. For the two presidential elections during that period, we collected data through interviews with knowledgeable individuals and the use of secondary sources.
Keywords: 330; campaign financing; Tanzania; Uganda; MP campaigns; Parliamentary campaigns; Primary campaigns; Presidential campaigns; goverment funding